STRATEGI ACTIVE LEARNING DALAM PEMBELAJARAN PAI - Homaedi Homaedi; Randi Suhendi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The problem of education today is the declining spirit of learners to learn,especially in religious learning. This is evidenced by the early learners stop learning in the mushalla in the villages. The students’ learning interest in Islamic Education courses is very low. Many factors cause this to happen. There is a conclusion that the trigger is the quality of teachers who are also low Islamic Education, either the quality of mastery of the material or mastery of learning methods. There is also an assume that the cause of low interest of learners to Islamic Education’s learning is because Islamic Education is not National examination, so they do not feel compelled to learn it. The one solution for this problem is the implementation of Active Learning on Islamic Education learning in schools. In this paper, Active Learning - with the various methods in it - is presented practicaly. This paper assists the Islamic Education learning practitioner in their instructional assignment. There are three methods are presented learning in this paper, they are Jigsaw, Numbered Head Together, and Think Pair and Share.